An update of new flood-irrigated rice cultivars in the SimulArroz model - Ribas, Giovana Ghisleni; Streck, Nereu Augusto; Duarte Junior, Ary José; Ribeiro, Bruna San Martin Rolin; Pilecco, Isabela Bulegon; Rossato, Ioran Guedes; Richter, Gean Leonardo; Bexaira, Kelin Pribs; Pereira, Vladison Fogliato; Zanon, Alencar Junior (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to model, in the SimulArroz model, the three flood-irrigated rice (Oryza sativa) cultivars currently most grown in the state of Rio Grande do Sul, Brazil. The experiments to calibrate and validate the model were conducted in the municipalities of Cachoeirinha, Santa Maria, Uruguaiana, Santa Vitória do Palmar, and Cachoeira do Sul during four crop seasons. The number of leaves, phenology, aboveground dry matter biomass, and yield of each cultivar were evaluated. The results showed a slight overestimate of the R1, R4, and R9 stages; however, overall, the SimulArroz model had a good performance in simulating rice phenology for the three studied genotypes. Furthermore, the model had a reasonable accuracy in simulating aboveground dry matter and yield. The root-mean-square error (RMSE) for aboveground dry matter (leaves, stems, panicles, and grains) ranged from 0.5 to 3.0 Mg ha-1. For yield, the RMSE ranged from 0.8 to 1.3 Mg ha-1. The calibration of the SimulArroz model is efficient in simulating the growth, development, and grain yield of the most important flood-irrigated rice cultivars in Southern Brazil and can be used to estimate harvest forecast and yield potential, as well for yield gap studies.